Socialization of IoT Technology Utilization in Monitoring and Analysis of Electricity Usage among Students at SMKN 10 Makassar - Mayasari, Fitriyanti; Muslimin, Zaenab; Ahmad, Andani; Areni, Intan Sari; ., Dewiani; Gunadin, Indar Chaerah; Salam, A. Ejah Umraeni; ., Wardi; Anshar, Muh.; Achmad, Andini Dani (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
The Community Service Program (PkM) conducted by the Department of Electrical Engineering aims to enhance the literacy and skills of students at SMKN 10 Makassar in understanding the concept of energy monitoring and the application of Internet of Things (IoT) technology as an innovative solution for energy management systems. The main problem identified in the school is the low awareness and understanding of energy efficiency, as well as the lack of monitoring tools capable of displaying real-time energy consumption data. Through socialization and training activities based on microcontroller technology, students were introduced to the working principles of current and voltage sensors, data transmission via the internet, and digital visualization of electrical energy consumption through IoT-based platforms. The activity evaluation was carried out using pre-test and post-test methods involving 25 students from the Electrical Engineering Department to measure comprehension improvement. The results showed a significant increase in two main aspects: understanding of the basic concepts of energy monitoring, which rose from 60% to 96%, and understanding of the integration of IoT in energy monitoring systems, which increased from 20% to 88%. These findings demonstrate that implementing IoT-based learning not only broadens students’ insights into energy efficiency but also strengthens their vocational competencies in electrical engineering through the application of intelligent technologies relevant to the needs of modern industry.